2007
DOI: 10.1111/j.1440-1754.2007.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting obesity in early adulthood in Japanese women

Abstract: (i) For a Japanese woman, BMI in childhood is a good indicator of young adult BMI, and has the possibility of becoming an important parameter to monitor obesity progression. (ii) Therefore, attempts to control obesity in elementary school girls are necessary. (iii) Parents' weights may potentially influence obesity in adulthood; however, further examination of other confounding factors is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 16 publications
(40 reference statements)
0
13
0
Order By: Relevance
“…The treatment of obesity, as a health disturbance due to excess weight after later childhood, is the third prevention strategy. We previously reported that 30% or less of women who were overweight at 3 and 6 years old continued to be overweight in adulthood (Table 8), and also showed that adiposity rebound (AR) generally occurred at the age of 7 in Japanese women (6). Moreover, an increase in BMI between 7 and 8 years of age showed a positive correlation with adult BMI.…”
Section: Prophylaxismentioning
confidence: 79%
See 1 more Smart Citation
“…The treatment of obesity, as a health disturbance due to excess weight after later childhood, is the third prevention strategy. We previously reported that 30% or less of women who were overweight at 3 and 6 years old continued to be overweight in adulthood (Table 8), and also showed that adiposity rebound (AR) generally occurred at the age of 7 in Japanese women (6). Moreover, an increase in BMI between 7 and 8 years of age showed a positive correlation with adult BMI.…”
Section: Prophylaxismentioning
confidence: 79%
“…BMI is considered to be a very simple measurement because it is calculated as body weight (kg)/height 2 (m 2 ). However, due to age-dependent variations in the BMI, as shown in Figure 3 (6) it is difficult to examine time-dependent changes based on absolute values. BMI percentiles and standard deviations specific to Japanese people have recently been determined (7,8).…”
Section: Indices To Measure Being Overweight and Obesitymentioning
confidence: 99%
“…Many studies have firmly recognized obesity as an independent determinant of cardiovascular diseases (CVD) [2][5]. Body mass index (BMI) and waist circumference (WC) are commonly recommended for the assessment of obesity [6], [7]. However, recent studies have challenged the relationship between obesity assessed by BMI or WC and CVD [8], [9].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of type 2 diabetes is expanding more rapidly in Asian than in Western countries, this is particularly so in younger age groups . In addition, a strong association between high body mass index (BMI) during childhood and obesity during adult life has been established .…”
mentioning
confidence: 99%